Design of hierarchical porous aluminas by using one-pot synthesis and different calcination temperatures - Passos, Aline R. [UNESP]; Martins, Leandro [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Springer, 2012)
Hierarchical aluminas with pore sizes ranging from a few nanometers to micrometers were obtained using an one-pot sol-gel synthesis. The aluminas were synthesized under acid conditions from aluminum isopropoxide in presence of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer template and decahydronaphthalene as emulsifier agent. High-resolution transmission electron microscopy, small-angle X-ray scattering, nitrogen physisorption isotherms and mercury intrusion porosimetry provided evidences of porous structure at different hierarchical levels. The produced aluminas possess hierarchical structure composed of different family of pores that coexist in form of cylinders, pyramids and stacking of platelets. The morphology observed by electron microscopy suggests that the cylindrical pores result from the stacking platelets and that the cylinders and pyramidal pores form the walls of macropores of circular section. These aluminas with hierarchical porous architecture present large surface areas (ca. 435 m(2) g(-1)) and pore volumes (ca. 2.1 cm(3) g(-1)), tunable pore-size distributions and good thermal stability.
Keywords: Hierarchical aluminas; Thermal stability; Porous materials; Mesopores; Macropores